Polyester film with high adhesion to UV material and preparation method thereof
By adding additives containing polar groups to the polyester film, the problem of low adhesion fastness between polyester film and UV materials is solved, high adhesion fastness and excellent optical and mechanical properties are achieved, and the pass rate of laser anti-counterfeiting film is improved.
Patent Information
- Application Number
- CN202411793394.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-12-09
AI Technical Summary
The low adhesion fastness of polyester films and UV materials leads to a low pass rate of laser anti-counterfeiting films. Existing methods such as the use of coatings will affect the optical and mechanical properties of polyester films.
By directly adding an additive containing polar groups to the polyester film, the polar group content on the surface of the polyester film is increased, thereby improving the adhesion fastness of UV materials. The specific method includes preparing the first additive and the second additive, and forming an additive with crosslinking and fluidity through the steps of first-stage coating, crosslinking, coating and crosslinking, respectively, to improve the adhesion performance of the polyester film.
The high adhesion fastness between polyester film and UV material is achieved, the pass rate of laser anti-counterfeiting film is improved, and the high transparency, mechanical properties and apparent properties of polyester film are maintained.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyester films, and in particular to a polyester film with high adhesion to UV materials and a preparation method thereof. Background Art
[0002] Polyester film has excellent optical properties, excellent air tightness and mechanical properties, such as extremely high transparency and gloss, and extremely low haze. Its toughness is the best among all thermoplastics, and its tensile strength and impact strength are also higher than other plastic films. It also has excellent dimensional stability, heat resistance, cold resistance, and oil resistance, and is suitable for the fields of printing and packaging technology.
[0003] Due to the excellent optical properties and dimensional stability of polyester film, it is widely used as a laser anti-counterfeiting base film in the preparation of laser anti-counterfeiting film. When preparing laser anti-counterfeiting film with polyester film as the laser anti-counterfeiting base film, it is necessary to first compound a layer of UV material on the polyester film, and then perform molding to prepare the laser anti-counterfeiting film. However, when compounding the polyester film with the UV material, there is a problem of low adhesion of the UV material on the surface of the polyester film, resulting in a low pass rate of the prepared laser anti-counterfeiting film.
[0004] After further analysis, it was found that the main components of UV materials are UV curing resin, photoinitiator, pigment filler, and additives. Among them, the commonly used UV curing resin is acrylic resin. However, due to the smooth surface of polyester film, few polar groups, low surface free energy, poor wettability and adhesion, the acrylic resin has low adhesion strength on the surface of polyester film and is easy to peel off. In order to solve the aforementioned problem of low adhesion strength, the most commonly used method is to add a layer of coating material between the UV material and the polyester film. The coating material can play a role of molecular bridging between the UYV material and the polyester film, thereby improving the adhesion strength of the UV material on the surface of the polyester film.
[0005] However, there are the following problems in the use of coating materials: first, the use of coating materials will affect the optical properties of polyester film, resulting in decreased transparency and glossiness of the polyester film and increased haze; second, the leveling properties of the coating material are greatly affected by temperature, and the leveling properties are poor at low temperatures, resulting in uneven coating during coating, which further leads to a decrease in the apparent performance of the prepared laser anti-counterfeiting film.
[0006] In order to solve the above problems, the inventors tried to directly add an additive containing a polar group into the polyester film, thereby introducing polar groups on the surface of the polyester film. However, due to the different light transmittances of the additive and polyester, the transparency and haze of the polyester film will be affected. In addition, the additive and polyester also have poor compatibility and poor dispersibility of the additive in polyester, which leads to a decrease in the mechanical properties and apparent properties of the prepared polyester film. Summary of the invention
[0007] In view of the shortcomings of the prior art, the present invention provides a polyester film with high adhesion to UV materials and a preparation method thereof. The prepared polyester film has high transparency, good mechanical properties and surface properties, low haze, and high adhesion to UV materials.
[0008] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:
[0009] A method for preparing a polyester film with high adhesion to UV materials, comprising the following steps: preparing a first auxiliary agent, preparing a second auxiliary agent, preparing raw materials, and melt extruding;
[0010] The preparation of the first auxiliary agent comprises the following steps: primary coating, primary crosslinking, secondary coating, and secondary crosslinking;
[0011] The primary coating comprises mixing fumed silica and deionized water, performing ultrasonic oscillation, controlling the frequency of the ultrasonic oscillation to be 20-30 kHz, and performing the ultrasonic oscillation for 15-20 min, and then mixing with an acetic acid aqueous solution of chitosan, stirring at room temperature, controlling the stirring speed to be 100-300 rpm, and performing the centrifugation, controlling the centrifugation speed to be 12000-13000 rpm, and performing the centrifugation for 5-6 min, taking the precipitate, washing it with deionized water for 3-4 times, and drying it to obtain the primary coated silica;
[0012] In the primary coating, the usage ratio of fumed silica, deionized water, and chitosan acetic acid aqueous solution is 1-1.1 kg: 18-20 L: 10-11 L;
[0013] The particle size of the fumed silica is 40 nm;
[0014] The preparation method of the chitosan acetic acid aqueous solution is as follows: chitosan, glacial acetic acid and deionized water are mixed, and then stirred at room temperature, and the stirring speed is controlled to be 100-300 rpm for 25-35 minutes to obtain the chitosan acetic acid aqueous solution;
[0015] In the preparation of the acetic acid aqueous solution of chitosan, the dosage ratio of chitosan, glacial acetic acid and deionized water is 0.1-0.12kg:0.15-0.18kg:10-11L;
[0016] The primary crosslinking comprises mixing the primary coated white carbon black and deionized water, stirring at room temperature, controlling the stirring speed to be 100-300 rpm, and the time to be 20-30 min, adding ammonia water dropwise while stirring until the pH value is 7.8-8.2, and continuing to stir for 5-10 min after the addition is completed, adding glutaraldehyde aqueous solution dropwise while stirring, and continuing to stir for 2-2.5 h after the addition is completed, centrifuging, controlling the centrifugal speed to be 12000-13000 rpm, and the time to be 5-6 min, taking the precipitate, washing it with deionized water for 3-4 times, and drying it to obtain the primary crosslinked white carbon black;
[0017] In the primary cross-linking, the material ratio of the primary coating white carbon black, deionized water, and glutaraldehyde aqueous solution is 1.05-1.1 kg: 14-15 L: 0.35-0.4 L;
[0018] The mass concentration of the ammonia water is 28%;
[0019] The mass concentration of the glutaraldehyde aqueous solution is 5%;
[0020] The dropping speed of the ammonia water is 10-20 mL / min;
[0021] The dropping speed of the glutaraldehyde aqueous solution is 30-40 mL / min;
[0022] The secondary coating comprises mixing primary cross-linked white carbon black, polyvinyl pyrrolidone and deionized water, stirring at room temperature, controlling the stirring speed to be 100-300 rpm, and the time to be 2-2.5 hours, centrifuging, controlling the centrifugal speed to be 12000-13000 rpm, and the time to be 5-6 minutes, taking the precipitate, washing it with deionized water for 3-4 times, and drying it to obtain secondary coated white carbon black;
[0023] In the secondary coating, the dosage ratio of primary cross-linked white carbon black, polyvinyl pyrrolidone and deionized water is 1.05-1.1kg:0.1-0.12kg:13-15L;
[0024] The secondary crosslinking comprises mixing the secondary coated white carbon black and deionized water, stirring at room temperature, controlling the stirring speed to be 100-300 rpm, and the time to be 20-30 min, adding the glutaraldehyde aqueous solution dropwise while stirring, and continuing to stir for 2-2.5 h after the addition is completed, centrifuging, controlling the centrifugal speed to be 12000-13000 rpm, and the time to be 5-6 min, taking the precipitate, washing it with deionized water for 3-4 times, and drying it to obtain the first auxiliary agent;
[0025] In the secondary crosslinking, the material ratio of the secondary coated white carbon black, deionized water, and glutaraldehyde aqueous solution is 1.05-1.1 kg: 14-15 L: 0.28-0.3 L;
[0026] The mass concentration of the glutaraldehyde aqueous solution is 5%;
[0027] The dropping speed of the glutaraldehyde aqueous solution is 30-40 mL / min;
[0028] The preparation of the second auxiliary agent comprises the following steps: coating and cross-linking;
[0029] The coating comprises mixing hyperbranched polyester Boltorn H20 and N,N-dimethylformamide, stirring at 50-55° C., controlling the stirring speed to 200-300 rpm, and the time to 30-40 min, adding primary cross-linked white carbon black, continuing to stir for 3-3.5 h, centrifuging, controlling the centrifugal speed to 13000-14000 rpm, and the time to 8-10 min, taking the precipitate, washing it with N,N-dimethylformamide for 3-4 times, and drying it to obtain a coating;
[0030] In the coating, the usage ratio of hyperbranched polyester Boltorn H20, N,N-dimethylformamide, and primary cross-linked white carbon black is 0.15-0.18kg:12-14L:0.8-0.9kg;
[0031] The primary cross-linked white carbon black is prepared according to the method of primary coating and primary cross-linking in preparing the first auxiliary agent;
[0032] The crosslinking comprises mixing the coating and deionized water, stirring at 50-55° C., controlling the stirring speed to 100-300 rpm, and the time to 20-30 min, adding glutaraldehyde aqueous solution dropwise while stirring, and continuing to stir for 2-2.5 h after the addition is completed, centrifuging, controlling the centrifugal speed to 13000-14000 rpm, and the time to 8-10 min, taking the precipitate, washing it with deionized water for 3-4 times, and drying it to obtain the second auxiliary agent;
[0033] In the cross-linking, the material ratio of the coating, deionized water, and glutaraldehyde aqueous solution is 0.85-0.95 kg: 12-14 L: 0.32-0.35 L;
[0034] The mass concentration of the glutaraldehyde aqueous solution is 2%;
[0035] The dropping speed of the glutaraldehyde aqueous solution is 30-40 mL / min;
[0036] The raw material preparation includes pre-crystallizing and drying the PET resin to obtain the treated PET resin, and then weighing the raw materials of layer A, layer B, and layer C respectively;
[0037] In the raw material preparation, the A layer raw material is composed of the following raw materials in parts by weight: 92-93 parts of the treated PET resin, 4-4.5 parts of the first auxiliary agent, and 3-3.5 parts of the second auxiliary agent; the B layer raw material is the treated PET resin; the C layer raw material is composed of the following raw materials in parts by weight: 92-93 parts of the treated PET resin, 4-4.5 parts of the first auxiliary agent, and 3-3.5 parts of the second auxiliary agent;
[0038] The mass ratio of the raw material of layer A, the raw material of layer B, and the raw material of layer C is 3-4:14-16:3-4;
[0039] The model of the PET resin used in the A-layer raw material, the B-layer raw material, and the C-layer raw material is FG600;
[0040] The melt extrusion comprises: feeding the raw material of layer A, the raw material of layer B and the raw material of layer C into a No. 1 twin-screw extruder, a single-screw extruder and a No. 2 twin-screw extruder for melt extrusion, and then cooling and solidifying on the surface of a casting roll, and then longitudinally stretching and transversely stretching to obtain a polyester film;
[0041] During the melt extrusion, the heating zone temperature of the No. 1 twin-screw extruder and the No. 2 twin-screw extruder is 256-265° C.;
[0042] The heating zone temperature of the single screw extruder is 270-285°C;
[0043] The longitudinal stretching temperature is 79-89°C, and the ratio is 3.3-3.6:1;
[0044] The transverse stretching is divided into six sections, namely, a preheating section, a stretching section, a shaping section, a first cooling section, a second cooling section, and a third cooling section. The temperature of the preheating section is 110-120°C, the temperature of the stretching section is 120-130°C, the ratio is 3.5-4:1, the temperature of the shaping section is 230-240°C, and the cooling section is divided into three sections. The temperature of the first cooling section is 145-150°C, the temperature of the second cooling section is 105-110°C, and the temperature of the third cooling section is 55-60°C.
[0045] A polyester film with high adhesion to UV materials prepared by the above-mentioned preparation method.
[0046] Compared with the prior art, the present invention has the following beneficial effects:
[0047] (1) The method for preparing a polyester film having high adhesion to UV materials of the present invention has high transparency and a light transmittance of 90.21-92.08%;
[0048] (2) The method for preparing a polyester film having high adhesion to UV materials of the present invention, wherein the prepared polyester film has low haze, the haze being 1.25-1.87%;
[0049] (3) The method for preparing a polyester film with high adhesion to UV materials of the present invention has good mechanical properties, a longitudinal tensile strength of 202-230 MPa, and a transverse tensile strength of 235-263 MPa;
[0050] (4) The method for preparing a polyester film with high adhesion to UV materials of the present invention has good appearance performance, a dynamic friction coefficient of 0.49-0.52, a static friction coefficient of 0.52-0.57, and a smooth appearance without bubbles or wrinkles;
[0051] (5) The method for preparing a polyester film having high adhesion strength to UV materials of the present invention, wherein the prepared polyester film has high adhesion strength to UV materials, the surface of the polyester film is coated with UV varnish and then cured, and then 3M 600 tape is used to adhere to the UV varnish layer of the laser anti-counterfeiting film, and then the tape is torn off, and the UV varnish layer does not have the problem of falling off. DETAILED DESCRIPTION
[0052] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific implementation methods of the present invention are now described.
[0053] Example 1
[0054] A method for preparing a polyester film with high adhesion to UV materials, specifically comprising:
[0055] 1. Preparation of the first auxiliary agent:
[0056] (1) Primary coating: 1 kg of fumed silica and 18 L of deionized water were mixed, and ultrasonic oscillation was performed at a frequency of 20 kHz for 15 min. The mixture was then mixed with 10 L of chitosan in acetic acid, and stirred at room temperature at a speed of 100 rpm for 2 h. The mixture was centrifuged at a speed of 12,000 rpm for 5 min. The precipitate was washed three times with deionized water and dried to obtain primary coated silica.
[0057] The particle size of the fumed silica is 40 nm;
[0058] The preparation method of the acetic acid aqueous solution of chitosan is as follows: 0.1 kg of chitosan, 0.15 kg of glacial acetic acid and 10 L of deionized water are mixed, and the mixture is stirred at room temperature, and the stirring speed is controlled to be 100 rpm for 25 min to obtain the acetic acid aqueous solution of chitosan;
[0059] (2) Primary crosslinking: 1.05 kg of primary coated white carbon black and 14 L of deionized water were mixed and stirred at room temperature at a speed of 100 rpm for 20 min. Ammonia water was added dropwise while stirring until the pH value was 7.8 at a speed of 10 mL / min. Stirring was continued for 5 min after the addition was completed. 0.35 L of glutaraldehyde aqueous solution was added dropwise while stirring at a speed of 30 mL / min. Stirring was continued for 2 h after the addition was completed. The mixture was centrifuged at a speed of 12,000 rpm for 5 min. The precipitate was taken and washed three times with deionized water and dried to obtain primary crosslinked white carbon black.
[0060] The mass concentration of the ammonia water is 28%;
[0061] The mass concentration of the glutaraldehyde aqueous solution is 5%;
[0062] (3) Secondary coating: 1.05 kg of primary cross-linked silica, 0.1 kg of polyvinyl pyrrolidone, and 13 L of deionized water were mixed, stirred at room temperature, and the stirring speed was controlled to 100 rpm for 2 h. The mixture was centrifuged at a speed of 12,000 rpm for 5 min. The precipitate was washed 3 times with deionized water, and dried to obtain secondary coated silica.
[0063] (4) Secondary crosslinking: 1.05 kg of secondary coated white carbon black and 14 L of deionized water were mixed and stirred at room temperature at a speed of 100 rpm for 20 min. 0.28 L of glutaraldehyde aqueous solution was added dropwise while stirring at a speed of 30 mL / min. After the addition, stirring was continued for 2 h. The mixture was centrifuged at a speed of 12,000 rpm for 5 min. The precipitate was taken and washed three times with deionized water and dried to obtain the first auxiliary agent.
[0064] The mass concentration of the glutaraldehyde aqueous solution is 5%;
[0065] 2. Preparation of the second auxiliary agent:
[0066] (1) Coating: 0.15 kg of hyperbranched polyester Boltorn H20 and 12 L of N,N-dimethylformamide were mixed, stirred at 50°C, the stirring speed was controlled at 200 rpm, the time was 30 min, 0.8 kg of primary cross-linked white carbon black was added, the stirring was continued for 3 h, the centrifugation was controlled at 13000 rpm, the time was 8 min, the precipitate was taken, washed with N,N-dimethylformamide for 3 times, and dried to obtain a coated material;
[0067] The primary cross-linked white carbon black is prepared by the method of step (1) primary coating and step (2) primary cross-linking in the preparation of the first auxiliary agent in step 1;
[0068] (2) Cross-linking: 0.85 kg of the coating material and 12 L of deionized water were mixed, stirred at 50°C, the stirring speed was controlled at 100 rpm, the time was 20 min, 0.32 L of glutaraldehyde aqueous solution was added dropwise while stirring, the dropping speed was controlled at 30 mL / min, stirring was continued for 2 h after the addition was completed, and the mixture was centrifuged at a speed of 13000 rpm for 8 min. The precipitate was taken, washed with deionized water for 3 times, and dried to obtain the second auxiliary agent;
[0069] The mass concentration of the glutaraldehyde aqueous solution is 2%;
[0070] 3. Raw material preparation: After pre-crystallization and drying of the PET resin, the treated PET resin is obtained, and then the raw materials of the A layer, B layer and C layer are weighed respectively, wherein the raw material of the A layer is composed of the following raw materials in parts by weight: 93 parts of the treated PET resin, 4 parts of the first auxiliary agent, and 3 parts of the second auxiliary agent; the raw material of the B layer is the treated PET resin; the raw material of the C layer is composed of the following raw materials in parts by weight: 93 parts of the treated PET resin, 4 parts of the first auxiliary agent, and 3 parts of the second auxiliary agent, and the mass ratio of the raw materials of the A layer, the B layer and the C layer is controlled to be 3:14:3;
[0071] The model of the PET resin used in the A-layer raw material, the B-layer raw material, and the C-layer raw material is FG600;
[0072] 4. Melt extrusion: The A layer raw material, the B layer raw material, and the C layer raw material are respectively put into the No. 1 twin-screw extruder, the single screw extruder, and the No. 2 twin-screw extruder for melt extrusion, and the heating zone temperature of the No. 1 twin-screw extruder and the No. 2 twin-screw extruder is controlled to be 256°C, and the heating zone temperature of the single screw extruder is 270°C. Then, after cooling and solidification on the surface of the casting roll, longitudinal stretching is performed, and the longitudinal stretching temperature is controlled to be 79°C, and the ratio is 3.3:1. Transverse stretching is performed, and the transverse stretching is divided into six sections, namely, a preheating section, a stretching section, a shaping section, a first cooling section, a second cooling section, and a third cooling section. Among them, the temperature of the preheating section is 110°C, the temperature of the stretching section is 120°C, the ratio is 3.5:1, the temperature of the shaping section is 230°C, and the cooling section is divided into three sections, the temperature of the first cooling section is 145°C, the temperature of the second cooling section is 105°C, and the temperature of the third cooling section is 55°C, to obtain a polyester film;
[0073] The polyester film had a thickness of 30 μm.
[0074] This embodiment also provides a polyester film with high adhesion to UV materials, which is prepared by the aforementioned preparation method.
[0075] Example 2
[0076] A method for preparing a polyester film with high adhesion to UV materials, specifically comprising:
[0077] 1. Preparation of the first auxiliary agent:
[0078] (1) Primary coating: 1.05 kg of fumed silica and 19 L of deionized water were mixed, and ultrasonic oscillation was performed at a frequency of 25 kHz for 18 min. The mixture was then mixed with 10.5 L of chitosan acetic acid aqueous solution, and stirred at room temperature at a speed of 200 rpm for 2 h. The mixture was centrifuged at a speed of 12,000 rpm for 5 min. The precipitate was washed three times with deionized water and dried to obtain primary coated silica.
[0079] The particle size of the fumed silica is 40 nm;
[0080] The preparation method of the acetic acid aqueous solution of chitosan is as follows: 0.11 kg of chitosan, 0.16 kg of glacial acetic acid, and 10.5 L of deionized water are mixed, and the mixture is stirred at room temperature, and the stirring speed is controlled to be 200 rpm for 30 minutes to obtain the acetic acid aqueous solution of chitosan;
[0081] (2) Primary crosslinking: 1.08 kg of primary coated white carbon black and 14.5 L of deionized water were mixed and stirred at room temperature at a speed of 200 rpm for 25 min. Ammonia water was added dropwise while stirring until the pH value was 8 at a speed of 20 mL / min. Stirring was continued for 8 min after the addition was completed. 0.38 L of glutaraldehyde aqueous solution was added dropwise while stirring at a speed of 30 mL / min. Stirring was continued for 2 h after the addition was completed. The mixture was centrifuged at a speed of 12,000 rpm for 5 min. The precipitate was taken and washed three times with deionized water and dried to obtain primary crosslinked white carbon black.
[0082] The mass concentration of the ammonia water is 28%;
[0083] The mass concentration of the glutaraldehyde aqueous solution is 5%;
[0084] (3) Secondary coating: 1.08 kg of primary cross-linked silica, 0.11 kg of polyvinyl pyrrolidone, and 14 L of deionized water were mixed, stirred at room temperature, and the stirring speed was controlled to 200 rpm for 2 h. The mixture was centrifuged at a speed of 12,000 rpm for 5 min. The precipitate was taken, washed with deionized water for 3 times, and dried to obtain secondary coated silica;
[0085] (4) Secondary crosslinking: 1.08 kg of secondary coated white carbon black and 14.5 L of deionized water were mixed and stirred at room temperature at a speed of 200 rpm for 25 min. 0.29 L of glutaraldehyde aqueous solution was added dropwise while stirring at a speed of 30 mL / min. After the addition, stirring was continued for 2 h. The mixture was centrifuged at a speed of 12,000 rpm for 5 min. The precipitate was taken and washed three times with deionized water and dried to obtain the first auxiliary agent.
[0086] The mass concentration of the glutaraldehyde aqueous solution is 5%;
[0087] 2. Preparation of the second auxiliary agent:
[0088] (1) Coating: 0.17 kg of hyperbranched polyester Boltorn H20 and 13 L of N,N-dimethylformamide were mixed, stirred at 52 °C, the stirring speed was controlled at 250 rpm, the time was 35 min, 0.85 kg of primary cross-linked white carbon black was added, the stirring was continued for 3 h, the centrifugation was controlled at a speed of 13000 rpm, the time was 9 min, the precipitate was taken, washed with N,N-dimethylformamide for 3 times, and dried to obtain a coated material;
[0089] The primary cross-linked white carbon black is prepared by the method of step (1) primary coating and step (2) primary cross-linking in the preparation of the first auxiliary agent in step 1;
[0090] (2) Cross-linking: 0.9 kg of the coating material and 13 L of deionized water were mixed, stirred at 52 °C, the stirring speed was controlled at 200 rpm, the time was 25 min, 0.34 L of glutaraldehyde aqueous solution was added dropwise while stirring, the dropping speed was controlled at 30 mL / min, stirring was continued for 2 h after the addition was completed, and the mixture was centrifuged at a speed of 13000 rpm for 9 min. The precipitate was taken, washed with deionized water for 3 times, and dried to obtain the second auxiliary agent;
[0091] The mass concentration of the glutaraldehyde aqueous solution is 2%;
[0092] 3. Raw material preparation: After pre-crystallization and drying of the PET resin, the treated PET resin is obtained, and then the raw materials of the A layer, B layer and C layer are weighed respectively, wherein the raw material of the A layer is composed of the following raw materials in parts by weight: 92.5 parts of the treated PET resin, 4.3 parts of the first auxiliary agent, and 3.2 parts of the second auxiliary agent; the raw material of the B layer is the treated PET resin; the raw material of the C layer is composed of the following raw materials in parts by weight: 92.5 parts of the treated PET resin, 4.3 parts of the first auxiliary agent, and 3.2 parts of the second auxiliary agent, and the mass ratio of the raw materials of the A layer, the B layer and the C layer is controlled to be 3.5:15:3.5;
[0093] The model of the PET resin used in the A-layer raw material, the B-layer raw material, and the C-layer raw material is FG600;
[0094] 4. Melt extrusion: The A layer raw material, the B layer raw material, and the C layer raw material are respectively put into the No. 1 twin-screw extruder, the single screw extruder, and the No. 2 twin-screw extruder for melt extrusion, and the heating zone temperature of the No. 1 twin-screw extruder and the No. 2 twin-screw extruder is controlled to be 260°C, and the heating zone temperature of the single screw extruder is 280°C. Then, after cooling and solidification on the surface of the casting roll, longitudinal stretching is performed, and the longitudinal stretching temperature is controlled to be 85°C, and the ratio is 3.5:1. Transverse stretching is performed, and the transverse stretching is divided into six sections, namely, a preheating section, a stretching section, a shaping section, a first cooling section, a second cooling section, and a third cooling section. Among them, the temperature of the preheating section is 115°C, the temperature of the stretching section is 125°C, the ratio is 3.8:1, the temperature of the shaping section is 235°C, and the cooling section is divided into three sections, the temperature of the first cooling section is 148°C, the temperature of the second cooling section is 108°C, and the temperature of the third cooling section is 58°C, to obtain a polyester film;
[0095] The polyester film had a thickness of 19 μm.
[0096] This embodiment also provides a polyester film with high adhesion to UV materials, which is prepared by the aforementioned preparation method.
[0097] Example 3
[0098] A method for preparing a polyester film with high adhesion to UV materials, specifically comprising:
[0099] 1. Preparation of the first auxiliary agent:
[0100] (1) Primary coating: 1.1 kg of fumed silica and 20 L of deionized water were mixed, and ultrasonic oscillation was performed at a frequency of 30 kHz for 20 min. The mixture was then mixed with 11 L of chitosan acetic acid aqueous solution, and stirred at room temperature at a speed of 300 rpm for 2.5 h. The mixture was centrifuged at a speed of 13,000 rpm for 6 min. The precipitate was washed 4 times with deionized water and dried to obtain primary coated silica.
[0101] The particle size of the fumed silica is 40 nm;
[0102] The preparation method of the acetic acid aqueous solution of chitosan is as follows: 0.12 kg of chitosan, 0.18 kg of glacial acetic acid, and 11 L of deionized water are mixed, and the mixture is stirred at room temperature, and the stirring speed is controlled to be 300 rpm for 35 minutes to obtain the acetic acid aqueous solution of chitosan;
[0103] (2) Primary crosslinking: 1.1 g of primary coated white carbon black and 15 L of deionized water were mixed and stirred at room temperature. The stirring speed was controlled at 300 rpm for 30 min. Ammonia water was added dropwise while stirring until the pH value was 8.2. The dropping speed was controlled at 20 mL / min. Stirring was continued for 10 min after the addition. 0.4 L of glutaraldehyde aqueous solution was added dropwise while stirring. The dropping speed was controlled at 40 mL / min. Stirring was continued for 2.5 h after the addition. The mixture was centrifuged at a speed of 13000 rpm for 6 min. The precipitate was taken and washed 4 times with deionized water and dried to obtain primary crosslinked white carbon black.
[0104] The mass concentration of the ammonia water is 28%;
[0105] The mass concentration of the glutaraldehyde aqueous solution is 5%;
[0106] (3) Secondary coating: 1.1 kg of primary cross-linked silica, 0.12 kg of polyvinyl pyrrolidone, and 15 L of deionized water were mixed, stirred at room temperature, the stirring speed was controlled to 300 rpm, the time was 2.5 h, centrifuged, the centrifugal speed was controlled to 13000 rpm, the time was 6 min, the precipitate was taken, washed with deionized water for 4 times, and dried to obtain secondary coated silica;
[0107] (4) Secondary crosslinking: 1.1 kg of secondary coated white carbon black and 15 L of deionized water were mixed and stirred at room temperature. The stirring speed was controlled at 300 rpm for 30 min. 0.3 L of glutaraldehyde aqueous solution was added dropwise while stirring. The dropping speed was controlled at 40 mL / min. After the addition was completed, stirring was continued for 2.5 h. The mixture was centrifuged at a speed of 13000 rpm for 6 min. The precipitate was taken and washed 4 times with deionized water and dried to obtain the first auxiliary agent.
[0108] The mass concentration of the glutaraldehyde aqueous solution is 5%;
[0109] 2. Preparation of the second auxiliary agent:
[0110] (1) Coating: 0.18 kg of hyperbranched polyester Boltorn H20 and 14 L of N,N-dimethylformamide were mixed, stirred at 55 °C, the stirring speed was controlled at 300 rpm, the time was 40 min, 0.9 kg of primary cross-linked white carbon black was added, the stirring was continued for 3.5 h, the centrifugation was controlled at a speed of 14000 rpm, the time was 10 min, the precipitate was taken, washed with N,N-dimethylformamide for 4 times, and dried to obtain a coated material;
[0111] The primary cross-linked white carbon black is prepared by the method of step (1) primary coating and step (2) primary cross-linking in the preparation of the first auxiliary agent in step 1;
[0112] (2) Cross-linking: 0.95 kg of the coating material and 14 L of deionized water were mixed and stirred at 55°C at a speed of 300 rpm for 30 min. 0.35 L of glutaraldehyde aqueous solution was added dropwise while stirring at a speed of 40 mL / min. After the addition, stirring was continued for 2.5 h. The mixture was centrifuged at a speed of 14,000 rpm for 10 min. The precipitate was washed four times with deionized water and dried to obtain a second auxiliary agent.
[0113] The mass concentration of the glutaraldehyde aqueous solution is 2%;
[0114] 3. Raw material preparation: After pre-crystallization and drying of the PET resin, the treated PET resin is obtained, and then the raw materials of the A layer, B layer and C layer are weighed respectively, wherein the raw material of the A layer is composed of the following raw materials in parts by weight: 92 parts of the treated PET resin, 4.5 parts of the first auxiliary agent, and 3.5 parts of the second auxiliary agent; the raw material of the B layer is the treated PET resin; the raw material of the C layer is composed of the following raw materials in parts by weight: 92 parts of the treated PET resin, 4.5 parts of the first auxiliary agent, and 3.5 parts of the second auxiliary agent, and the mass ratio of the raw materials of the A layer, the B layer and the C layer is controlled to be 4:16:4;
[0115] The model of the PET resin used in the A-layer raw material, the B-layer raw material, and the C-layer raw material is FG600;
[0116] 4. Melt extrusion: The A layer raw material, the B layer raw material, and the C layer raw material are respectively put into the No. 1 twin-screw extruder, the single screw extruder, and the No. 2 twin-screw extruder for melt extrusion, and the heating zone temperature of the No. 1 twin-screw extruder and the No. 2 twin-screw extruder is controlled to be 265°C, and the heating zone temperature of the single screw extruder is 285°C. Then, after cooling and solidification on the surface of the casting roll, longitudinal stretching is performed, and the longitudinal stretching temperature is controlled to be 89°C, and the ratio is 3.6:1. Transverse stretching is performed, and the transverse stretching is controlled to be divided into six sections, namely, a preheating section, a stretching section, a shaping section, a first cooling section, a second cooling section, and a third cooling section. Among them, the temperature of the preheating section is 120°C, the temperature of the stretching section is 130°C, the ratio is 4:1, the temperature of the shaping section is 240°C, and the cooling section is divided into three sections, the temperature of the first cooling section is 150°C, the temperature of the second cooling section is 110°C, and the temperature of the third cooling section is 60°C, to obtain a polyester film;
[0117] The polyester film had a thickness of 12 μm.
[0118] This embodiment also provides a polyester film with high adhesion to UV materials, which is prepared by the aforementioned preparation method.
[0119] Comparative Example 1
[0120] On the basis of the method for preparing a polyester film with high adhesion to UV materials in Example 1, the first step of preparing the first auxiliary agent is omitted, and in the third step of raw material preparation, a fumed silica with a particle size of 40 nm is used instead of the first auxiliary agent.
[0121] The rest of the technical solutions are consistent with those in Example 1.
[0122] This comparative example also provides a polyester film with high adhesion to UV materials, which is prepared by the aforementioned preparation method.
[0123] Comparative Example 2
[0124] On the basis of the method for preparing a polyester film with high adhesion to UV materials in Example 1, the second step of preparing the second auxiliary agent is omitted, and in the third step of raw material preparation, a fumed silica with a particle size of 40 nm is used instead of the second auxiliary agent.
[0125] The rest of the technical solutions are consistent with those in Example 1.
[0126] This comparative example also provides a polyester film with high adhesion to UV materials, which is prepared by the aforementioned preparation method.
[0127] Test Example 1
[0128] The light transmittance, haze, dynamic friction coefficient, static friction coefficient, transverse tensile strength, and longitudinal tensile strength of the polyester films prepared in Examples 1-3 and Comparative Examples 1-2 were tested, and the appearance was observed. The test and observation results are as follows:
[0129]
[0130] Test Example 2
[0131] The adhesion strength of the polyester films prepared in Examples 1-3 and Comparative Examples 1-2 to the UV material was tested, and the test method and test results are as follows:
[0132] Pour UV varnish onto the polyester film surface and apply it evenly. The amount of UV varnish used is controlled to be 5g / cm 2 , and then stick it on the laser plate, flatten it, put the film side up, use a UV lamp to irradiate and cure the UV varnish, control the power of the UV lamp to 250W, and the irradiation and curing time to 10s to obtain a laser anti-counterfeiting film;
[0133] Then use 3M 600 tape to stick to the UV varnish layer of the laser anti-counterfeiting film, and then tear off the tape to observe whether the UV varnish layer falls off. If the UV varnish layer does not fall off after tearing off the tape, it means that the polyester film and the UV material have a high adhesion strength. The observation results are as follows:
[0134]
[0135] It can be seen from the results of Test Example 1 and Test Example 2 that the transmittance, haze, dynamic friction coefficient, static friction coefficient, transverse tensile strength, longitudinal tensile strength and appearance of the polyester films prepared in Comparative Example 1 and Comparative Example 2 are worse than those in Example 1, and the polyester film prepared in Comparative Example 1 still has the problem of easy falling off of the UV varnish layer after being combined with UV varnish.
[0136] The first auxiliary agent in Examples 1-3 is prepared by a primary coating and a secondary coating, wherein the primary coating is firstly mixing fumed silica with deionized water and then subjecting the mixture to ultrasonic vibration, dispersing the fumed silica in deionized water, then adding an acetic acid aqueous solution of chitosan, adsorbing chitosan through the adsorption of fumed silica, and then performing primary cross-linking, using glutaraldehyde to cross-link the chitosan on the surface of the fumed silica, thereby coating the surface of the fumed silica with a layer of cross-linked chitosan, the cross-linked chitosan can provide polar groups on the one hand, thereby improving the adhesion strength of the UV material on the surface of the polyester film, and on the other hand, can promote the fixation of chitosan on the surface of the fumed silica and improve the heat resistance of the chitosan; then performing a secondary coating, the secondary coating is to use a polyvinyl pyrrolidone aqueous solution to treat the fumed silica coated with the cross-linked chitosan, Polyvinyl pyrrolidone is adsorbed on the surface of fumed silica after cross-linking chitosan through intermolecular force, and finally secondary cross-linking is performed. Glutaraldehyde is used to cross-link polyvinyl pyrrolidone, which can fix polyvinyl pyrrolidone on the one hand and reduce the hydrophilicity of polyvinyl pyrrolidone on the other hand. In addition, by coating cross-linked chitosan and cross-linked polyvinyl pyrrolidone on the surface of fumed silica respectively, the mutual influence between cross-linked chitosan and cross-linked polyvinyl pyrrolidone is avoided. In the use of the first auxiliary agent, the outermost cross-linked polyvinyl pyrrolidone can promote dispersion and improve compatibility with polyester. Moreover, by coating and filling fumed silica with cross-linked chitosan and cross-linked polyvinyl pyrrolidone, the dispersion of fumed silica is promoted, thereby improving the transparency, mechanical properties and apparent properties of the polyester film and reducing the haze of the polyester film.
[0137] The second auxiliary agent is prepared by coating and cross-linking. The first-level cross-linked white carbon black obtained by the preparation of the first auxiliary agent is used in the coating. Then, the first-level cross-linked white carbon black is treated with an N,N-dimethylformamide solution of a hyperbranched polyester Boltorn H20. The hyperbranched polyester Boltorn H20 can adhere to the surface of the first-level cross-linked white carbon black to obtain a coating of the surface coating and the hyperbranched polyester Boltorn H20. Then, the hyperbranched polyester Boltorn H20 is cross-linked with glutaraldehyde during the cross-linking process to fix the hyperbranched polyester Boltorn H20 on the surface of the second auxiliary agent. The outermost layer of the hyperbranched polyester Boltorn H20 can promote dispersion and improve compatibility with polyester, thereby improving the transparency, mechanical properties, and apparent properties of the polyester film and reducing the haze of the polyester film.
[0138] Polyvinyl pyrrolidone in the first auxiliary agent and hyperbranched polyester Boltorn H20 in the second auxiliary agent are commonly used additives in polyester films. Polyvinyl pyrrolidone and hyperbranched polyester Boltorn H20 are used to coat fumed silica whose surface is coated with cross-linked chitosan respectively, and the fluidity of polyvinyl pyrrolidone is used to promote the dispersion of fumed silica, and the cross-linking property of hyperbranched polyester Boltorn H20 is used to promote the cross-linking of fumed silica inside the polyester film, so that fumed silica exists in two states in the polyester film. The fumed silica combined with polyvinyl pyrrolidone can fix chitosan and provide polar groups through chitosan, and the fumed silica combined with hyperbranched polyester Boltorn H20 can increase the cross-linking density inside the polyester film, and the role of chitosan is mainly to combine more hyperbranched polyester Boltorn H20 in the coating.
[0139] Unless otherwise specified, all percentages used in the present invention are by mass.
[0140] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a polyester film having high adhesion to UV materials, characterized in that: The method comprises the following steps: preparing a first auxiliary agent, preparing a second auxiliary agent, preparing raw materials, and melt extruding; The preparation of the first auxiliary agent comprises the following steps: primary coating, primary crosslinking, secondary coating, and secondary crosslinking; The primary coating comprises mixing fumed silica and deionized water, performing ultrasonic vibration, and then mixing with an acetic acid aqueous solution of chitosan, stirring at room temperature, centrifuging, taking a precipitate, washing and drying to obtain a primary coated silica; The primary crosslinking comprises mixing the primary coated white carbon black and deionized water, stirring at room temperature, adjusting the pH to 7.8-8.2, continuing stirring after the dropwise addition, dropping the glutaraldehyde aqueous solution while stirring, continuing stirring after the dropwise addition, centrifuging, taking the precipitate, washing and drying to obtain the primary crosslinked white carbon black; The secondary coating comprises mixing primary cross-linked white carbon black, polyvinyl pyrrolidone and deionized water, stirring at room temperature, centrifuging, taking a precipitate, washing and drying, and obtaining a secondary coated white carbon black; The secondary crosslinking comprises mixing the secondary coated white carbon black and deionized water, stirring at room temperature, adding glutaraldehyde aqueous solution dropwise while stirring, continuing to stir after the addition is completed, centrifuging, taking the precipitate, washing and drying to obtain the first auxiliary agent; The preparation of the second auxiliary agent comprises the following steps: coating and cross-linking; The coating comprises mixing hyperbranched polyester Boltorn H20 and N,N-dimethylformamide, stirring at 50-55° C., adding primary cross-linked white carbon black, continuing stirring, centrifuging, taking a precipitate, washing and drying, and obtaining a coating; The cross-linking comprises mixing the coated material and deionized water, stirring at 50-55° C., adding glutaraldehyde aqueous solution dropwise while stirring, continuing stirring after the addition is completed, centrifuging, taking the precipitate, washing and drying, and obtaining the second auxiliary agent; The raw material preparation includes pre-crystallizing and drying the PET resin to obtain the treated PET resin, and then weighing the raw materials of layer A, layer B, and layer C respectively; In the raw material preparation, the A layer raw material is composed of the following raw materials in parts by weight: 92-93 parts of the treated PET resin, 4-4.5 parts of the first auxiliary agent, and 3-3.5 parts of the second auxiliary agent; the B layer raw material is the treated PET resin; the C layer raw material is composed of the following raw materials in parts by weight: 92-93 parts of the treated PET resin, 4-4.5 parts of the first auxiliary agent, and 3-3.5 parts of the second auxiliary agent; In the melt extrusion, the raw materials of layer A, layer B and layer C are respectively put into No. 1 twin-screw extruder, single-screw extruder and No. 2 twin-screw extruder for melt extrusion, and then cooled and solidified on the surface of the casting roll, and then stretched longitudinally and transversely to obtain a polyester film.
2. The method for preparing a polyester film having high adhesion to UV materials according to claim 1, characterized in that: In the primary coating, the usage ratio of fumed silica, deionized water, and chitosan acetic acid aqueous solution is 1-1.1 kg: 18-20 L: 10-11 L; The particle size of the fumed silica is 40 nm; The frequency of the ultrasonic oscillation is 20-30kHz, and the duration is 15-20min; The preparation method of the chitosan acetic acid aqueous solution is as follows: chitosan, glacial acetic acid and deionized water are mixed, and then stirred at room temperature to obtain the chitosan acetic acid aqueous solution; In the preparation of the acetic acid aqueous solution of chitosan, the usage ratio of chitosan, glacial acetic acid and deionized water is 0.1-0.12kg:0.15-0.18kg:10-11L.
3. The method for preparing a polyester film having high adhesion to UV materials according to claim 1, characterized in that: In the primary cross-linking, the material ratio of the primary coating white carbon black, deionized water, and glutaraldehyde aqueous solution is 1.05-1.1 kg: 14-15 L: 0.35-0.4 L; The mass concentration of the glutaraldehyde aqueous solution is 5%; The dropping speed of the glutaraldehyde aqueous solution is 30-40 mL / min.
4. The method for preparing a polyester film having high adhesion to UV materials according to claim 1, characterized in that: In the secondary coating, the usage ratio of primary cross-linked white carbon black, polyvinyl pyrrolidone and deionized water is 1.05-1.1 kg: 0.1-0.12 kg: 13-15 L.
5. The method for preparing a polyester film having high adhesion to UV materials according to claim 1, characterized in that: In the secondary crosslinking, the material ratio of the secondary coated white carbon black, deionized water, and glutaraldehyde aqueous solution is 1.05-1.1 kg: 14-15 L: 0.28-0.3 L; The mass concentration of the glutaraldehyde aqueous solution is 5%; The dropping speed of the glutaraldehyde aqueous solution is 30-40 mL / min.
6. The method for preparing a polyester film having high adhesion to UV materials according to claim 1, characterized in that: In the coating, the usage ratio of hyperbranched polyester Boltorn H20, N,N-dimethylformamide, and primary cross-linked white carbon black is 0.15-0.18kg:12-14L:0.8-0.9kg; The primary cross-linked white carbon black is prepared according to the method of primary coating and primary cross-linking in preparing the first auxiliary agent.
7. The method for preparing a polyester film having high adhesion to UV materials according to claim 1, characterized in that: In the cross-linking, the material ratio of the coating, deionized water, and glutaraldehyde aqueous solution is 0.85-0.95 kg: 12-14 L: 0.32-0.35 L; The mass concentration of the glutaraldehyde aqueous solution is 2%; The dropping speed of the glutaraldehyde aqueous solution is 30-40 mL / min.
8. The method for preparing a polyester film having high adhesion to UV materials according to claim 1, characterized in that: In the raw material preparation, the mass ratio of the A layer raw material, the B layer raw material, and the C layer raw material is 3-4:14-16:3-4; The model of the PET resin used in the A-layer raw material, the B-layer raw material, and the C-layer raw material is all FG600.
9. The method for preparing a polyester film having high adhesion to UV materials according to claim 1, characterized in that: During the melt extrusion, the heating zone temperature of the No. 1 twin-screw extruder and the No. 2 twin-screw extruder is 256-265° C.; The heating zone temperature of the single screw extruder is 270-285°C; The longitudinal stretching temperature is 79-89°C, and the ratio is 3.3-3.6:1; The transverse stretching is divided into six sections, namely, a preheating section, a stretching section, a shaping section, a first cooling section, a second cooling section, and a third cooling section. The temperature of the preheating section is 110-120°C, the temperature of the stretching section is 120-130°C, the ratio is 3.5-4:1, the temperature of the shaping section is 230-240°C, and the cooling section is divided into three sections. The temperature of the first cooling section is 145-150°C, the temperature of the second cooling section is 105-110°C, and the temperature of the third cooling section is 55-60°C.
10. A polyester film having high adhesion to UV materials, prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Thin film with base and method for producing same
CA2836038A1
Preparation method of hyperbranched polyester-polyvinyl alcohol pervaporation membrane
CN103331109A